A comparison between Trichomoniasis Infection and other Vaginal Infection among Females in Baghdad Governorate- Iraq - Saheb, Entsar J.; Kuba , Rash H.; Zghair , Khawla H.; Mosa, Israa S. (Iraqi Journal of Science, 2022)
Trichomoniasis is a parasitic disease caused by the protozoan Trichomonas vaginalis. It is the most common sexually transmitted protozoal infection. There is no estimated of infection intensity among reproductive-age females. Further studies of the infection intensity of trichomoniasis and other vaginal infection will highlight the importance of this pathogen as a public health problem. A total of 614 females from Baghdad city were screened for T. vaginalis from March 2015 to September 2015. Females aged 13–61 years old provided vaginal swab specimens. The vaginal fluids extracted from these swabs were checked for the presence of T. vaginalis and other vaginal infection using microscopic examination. Overall, 525 (85.5%) of 614 was screened positive for T. vaginalis, 89 of 614 females gave negative results for T. vaginalis instead; they were infected with other vaginal infection. In tested females, 82 (13.36%) of the females were infected with bacteria (including Haemophilus vaginalis, Escherichia coli and Pseudomonas); 7 (1.14%) of females was infected with Monilia. In addition, the main age group of infected females concentrated in (more than 30 years) which recorded a higher rate of infection. There were 122 (85.31%) of patients had (4) pus cells per field of microscope in Trichomonas infection, 29 (69.05%) of patients had (2) pus cells per field of microscope in bacterial infection, and 2 (33.33%) of patients had (2) pus cells per field of microscope in Monilia infection that was statistically significant. Taking together, the results of this study demonstrate that T. vaginalis is endemic of females in Baghdad city and has a higher intensity rate compare with females infect with bacteria or Monilia. A prevention strategy of T. vaginalis infection could control the transmission of this parasite.